(untitled) (Journal of Environmental Microbiology and Toxicology, 2022)
Phenol, in particular, is one of several dangerous synthetic compounds created by humans. There were more than 80,000 chemicals produced in the US for industrial use, and many of these are phenol and phenolic compounds that end up in the environment without being subjected to adequate safety assessment. There are several types of bacteria that may use phenol as a carbon source, making bioremediation of this dangerous material a promising possibility. We found that at very high concentrations of phenol, the growth rate of Pseudomonas putida NAUN-16 was significantly slowed down. The primary growth model modified Gompertz was utilized to obtain the growth parameter specific growth rate. In this study, we continue the work by further modelling the effect of substrate or phenol on the growth rate of the bacterium using several substrate inhibition kinetic models such as Monod, Haldane, Teissier, Aiba, Yano and Koga, Han and Levenspiel, Luong, Moser, Webb and Hinshelwood. The resultant fittings show appreciable fitting with the exception of the Monod model. The Teissier model, as opposed to the more widely used Haldane model, better suited the growth rate data at different concentrations of phenol as judged by the results of the RMSE, AICc, adjustedR2, F-test, and bias and accuracy factor. The designated values of the Teissier constants were maximal reduction rate, half saturation constant for maximal reduction and half inhibition constant which are symbolized by max, Ks and Ki were 0.150 1/hr (95% confidence interval 0.120 to 0.180), 162.19 mg/L (95% C.I.55.58 to 268.79) and 1291.94 mg/L (95% C.I. 1067.24 to 1516.65), respectively. The value generated from curve fitting interpolation should not be taken as the actual value and it should be warned of this as the true mumax should be where the gradient for the slope is zero and in this case the value was approximately 0.097 1/h at 385 mg/L phenol.